Rola biegłego w przeprowadzaniu oględzin w sprawach o zabójstwo: brak - Juszka, Kazimiera; Juszka, Karol (Studia Prawnoustrojowe, 2019)
This article presents the role of an expert witness during an inspection in capital crimes. An analysis was conducted of court and prosecutorial records which involved inspections in murder cases. The presentation is concentrated on doctrinal and judicial analyses from a detective and evidential point of view in sequential stages of criminal proceedings